The control scheme of vehicle steer by wire system by using hybrid single input fuzzy logic controller and PID controller - Mohd Zaidi, Mohd Tumari; Wan Norhisyam, Abd Rashid; Ab Wafi, Ab Aziz; Shahrizal, Saat; Mohd Helmi, Suid (Centre for Advanced Research on Energy, 2018)
The elimination of mechanical link between the steering wheel and front wheel of Vehicle Steer by Wire (VSBW) system makes the traditional model-based control techniques complex and difficult to synthesize in practice. This paper presents investigations of hybrid single input fuzzy logic controller (SIFLC) and PID controller for directional control and wheel synchronization of a VSBW system. The SIFLC reduces the conventional two-input FLC (CFLC) to a single input single output (SISO) controller. The implementation environment is developed within Matlab/Simulink software for evaluation of performance in terms of input tracking capability, wheel synchronization and time response specifications.